Cowboys - Silcott, Philip B.; Rogers, Martin, 1949- ([Washington] : National Geographic Society, 1975)
Gives an account of the life of a contemporary cowboy and his cattle ranch.
Keywords: Cowboys -- West (U.S.) -- Juvenile literature; Cowboys; West (U.S.) -- Description and travel -- 1951-1980 -- Juvenile literature